Technology transfer and enterprise performance: a firm-level analysis in China - Bilgin, Mehmet Huseyin; Lau, Chi Keung Marco; Karabulut, Gokhan (Journal of Business Economics and Management, 2012)
This paper attempts to explore the relationship between openness and a Chinese firm's productivity using 1999–2002 panel data on 26 industries covering 2400 enterprises. The current literature has focused mainly on the relationship between productivity and exports, using country-level data, leaving a gap in the relationship between imports and productivity unfilled, in particular at the firm specific level. However, our study complements the existing literature by using the latest set of data, and more importantly, by examining the effects of exports and importing machinery on the firm's performance. Using the dynamic panel data econometrics technique, we find evidence that firms can improve productivity by importing more capital good and utilizing foreign technologies from technologically advanced economies. Finally the effects of importing capital goods on productivities and that of exporting activities are compared.